Analysis of multiple virus-infected grapevine plant reveals persistence but uneven virus distribution - Kominek, P; Glasa, M; Kominkova, M (Acta virologica, 2009)
LN33 grapevine plants were artificially inoculated with budwoods originating from a field-cultivated Traminer grapevine which was naturally infected with Grapevine leafroll-associated virus 1 (GLRaV-1), Grapevine virus A (GVA), Grapevine virus B (GVB), Rupestris stem pitting-associated virus (RSPaV), and an unclassified tymovirus. Four years after inoculation, a comparison of the cane weights between healthy and infected grapevines did not show any significant difference. Corky bark symptoms or destructive effects of GVB infection never appeared on the infected grapevines. Dormant canes, sampled before the beginning of the vegetation period, were used for detection of grapevine viruses by ELISA or RT-PCR. ELISA turned out unexpectedly to be more effective than RT-PCR for detecting GLRaV-1 probably due to an insufficient specificity of the primers used, not reflecting the actual genetic variability of the virus. Distribution of viruses in the infected grapevines showed a different degree of irregularity in dependence on individual viruses. Therefore, in order to properly verify the sanitary status of grapevines under testing, several random samples from different parts of a tested plant have to be analyzed.
Keywords: Flexiviridae; Vitis; protilátky virové; polymerázová řetězová reakce s reverzní transkripcí; Antibodies, Viral; ELISA; Plant Viruses; Reverse Transcriptase Polymerase Chain Reaction; Plant Diseases; rostlinné viry; nemoci rostlin; Closteroviridae; Enzyme-Linked Immunosorbent Assay